Tracy Pintchman and Rita D. Sherma (eds), Woman and Goddess in Hinduism: Reinterpretations and Re-envisionings - Ferrari, Fabrizio M. (Religions of South Asia, 2013)
Tracy Pintchman and Rita D. Sherma (eds), Woman and Goddess in Hinduism: Reinterpretations and Re-envisionings. New York: Palgrave Macmillan, 2011. Ix + 243 pp. £55.00. ISBN 9780230113695 (hardback).